Analisis Pergerakan Kendaraan di Area Airside Terhadap Keselamatan Penerbangan Bandar Udara Domine Eduard Osok Sorong - Nur, Mulyadi (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
This research the contributing factor the provision of air traffic services. The factors are the influence of operational vehicle activity in the airside to aviation safety. The purpose to determine the effect of operational vehicle activities in the airside area to the aviation safety at Airport Sorong. Passenger movement at parking stand that still using the simple concept unavailable (markings on the apron) caused doubt in giving the distance movement area of vehicles on the airside area of Airport Sorong not well coordinated as they move flexibly because there are no SOP, guidance line and access road, and potential conflicts between taxiing aircraft with vehicle for example a passenger shuttle bus the process of loading an unloading safe between parking stand. Maneuvering taxi reached the gate position with the help of towing tractor with a lot of more skilled officers. It is recommended to make SOP for vehicles operating on the airside and changing the concept of aircraft parking stands from simple concept into line concept with the push-back system and Management apron by adding markings on the apron in order to avoid any doubt in providing secure distance between parking stands for the achievement of security, efficiency so that the use of the apron can be more optimal.